A Feminist Approach in ‘A Room Of One’s Own’ by Virginia Woolf - Sesilia Krisfianti (ESENSI LINGUA, 2023)
This research is to discuss Virginia Woolf's views on gender equality as well as the strengths and weaknesses of feminist theory. For feminist ideas, Woolf's debut novels A Room of One's Own and Orlando are crucial works. I'll attempt to focus on Virginia Woolf's book A Room of One's Own, which is regarded as her most significant work, especially in this study. Virginia Woolf produced several books and essays regarding gender discrimination. She focused mainly on equality. Woolf delivered several lectures on women in literature. In 1928, Woolf published Orlando, and in 1929, she published A Room of One's Own, her first work of feminism. She focused mainly on women and literature in this book; also, she described the difficulties they had encountered. In Orlando, she describes the struggle between genders.